Permeability properties of plastics and elastomers : a guide to packaging and barrier materials - Massey, Liesl K. (PDL handbook series., 2003)
This extensively revised and updated second edition of the only data handbook available on the properties of commercial polymeric films details the permeability characteristics of over 125 major plastic and elastomer packaging materials. New to this edition are 92 resin chapters containing textual summary information including: category, general description, processing methods, applications, and general permeability considerations for water vapor, oxygen, and other gases including aroma and flavor. The product data is presented in graphical and tabular format, retaining the familiar format of the first edition and allowing easy comparison between materials and test conditions.